ZAKIAH DARADJAT DAN PEMIKIRANNYA TENTANG PERAN PENDIDIKAN ISLAM DALAM KESEHATAN MENTAL - Muhammad Mawangir (JIA (Jurnal Ilmu Agama), 2015)
Zakiah Daradjat is the Indonesia’s prominent scholar on Islamic psychology. She focuses her study on the Islamic education psychology. Education according to Zakiah is the system that has to include the whole human aspects not only including faith, srituals, and values but also human development on mental and physical aspects.  The role of Islamic education according to Zakiah is the guidance of human life as the savior of human crysis, maintaining the order of human life, and moral control. In sum Islamic education can have the function on therapy on mental illness.